Protection against fire (Guidance note (Institution of Electrical Engineers), 2003)
A guide to the wiring regulations for protection against fire. It is part of a series of guidance notes, each of which enlarges upon the particular requirements of a part of the 16th edition wiring regulations. The text is cross-referenced to the regulations and aligns with BS 7671:2001.